One Factor at A Time based optimization of protease from poultry associated Bacillus licheniformis - Ameer Khusro (Journal of Applied Pharmaceutical Science, 2016)
Bacteria were isolated from poultry farm of Guduvanchery, Tamil Nadu, India and exhibited variable protease activity on skim milk agar plates. Of 10 bacterial isolates screened, Bacillus licheniformis strain 018 was observed as a hyperprotease producer and it was further characterized using biochemical and molecular tools. Protease production from the isolate was enhanced by optimizing the culture conditions using One Factor at A Time (OFAT) method. The bacteria exhibited its optimal enzyme activity at pH- 9.0, temperature- 35â°C, agitation speed- 130 rpm, incubation time- 24 h, carbon source- casein and nitrogen source- yeast extract. On the other hand, the crude proteases were found to be significantly active and stable at broad range of pH (5.0-9.0) and temperature (30-60â°C). To the best of my knowledge this is the first report on the production and enhancement of alkaline protease from poultry farm isolate using OFAT method. Stability of the enzyme at high temperature and pH can be explored for varied industrial applications.
Keywords: Alkaline protease,Bacillus licheniformis,OFAT,Poultry farm.